2013
DOI: 10.1055/s-0033-1343775
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Preeclampsia in Twin Pregnancies

Abstract: In twin pregnancy, the risk factors independently associated with preeclampsia are egg donation and prepregnancy obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…Meanwhile, risk factors associated with PE or IUGR in singleton pregnancy had inability to predict PE or IUGR in twin pregnancy (aside from obesity and egg donation for PE). [ 4 23 24 ] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, risk factors associated with PE or IUGR in singleton pregnancy had inability to predict PE or IUGR in twin pregnancy (aside from obesity and egg donation for PE). [ 4 23 24 ] …”
Section: Discussionmentioning
confidence: 99%
“…Recently, multiple studies have focused on the incidence and risk factors of twin pregnancies with PE, [ 48 ] but inadequate data exist regarding the clinical characteristics and perinatal outcomes of twin pregnancies with PE. [ 912 ] It is acknowledged that PE increases the risk of adverse maternal–neonatal outcomes mainly from data of singleton pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Kehamilan kembar berada pada peningkatan risiko hampir semua komplikasi kehamilan bila dibandingkan dengan kehamilan tunggal (Fox et al, 2014).…”
Section: Hubungan Kehamilan Kembar Dengan Kejadian Preeklampsiaunclassified
“…In a study by Levron et al ( 317 ), adjustment for maternal age, gravidity, parity, and chronic hypertension revealed that oocyte donation was independently associated with a higher rate of hypertensive diseases of pregnancy ( P < 0.01). In a twins study, Fox et al ( 318 ) found, on adjusted analysis, that the egg donation independently associated with PE (aOR 2.409, CI 1.051–5.524). The meta-anaysis of Thomopoulos et al ( 319 ) gave a risk ratio for egg donation of 3.60 (CI 2.56–5.05) over controls, a value similar to that of Blázquez et al ( 320 ).…”
Section: Evidence From Epidemiology—semen Can Be Protective Against Pmentioning
confidence: 99%